ANALISIS KINERJA KEUANGAN BANK PEMBANGUNAN DAERAH DALAM PERSAINGAN PERBANKAN - Juli Panglima Saragih (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2017)
Regional Development Bank (RDB) as part of banking industry is still needed to support financing for regional developmet. Due to tighted financial sector competition, Regional Development Bank should achieve market share in their playing field. Meanwhile, rigidity of regulation in banking sector, Regional Development Bank should also increase their business performance to maintain their standing position and increasing profitability, as well. This qualitative research uses analysis method of financial ratios and trend analysis of profit growth, as well. Data used in this research is financial data of banking industry from 2012 to 2016. This research summerizes that generally financial performance of Regional Dvelopment bank is good in 2012 to 2016. But, due to tight competition in financial market, the RDB could not compete with big private bank and state-owned bank where those banks have already been categorized as BUKU 3 and BUKU 4 category. On the other hand, most RDB are still categorized as BUKU 1 and BUKU 2 that have limited covering business, contrast to BUKU 3 and BUKU 4. Due to this condition, BPD should maintain its business stability and achieve excellent financial performance by obeying all regulations by managing asset and credit productively and profitably, implementing good corporate governance (GCG), as well as business transformation of RDB. Moreover, RDB should develop their infrastruktures to increase financial service for their debitor and customer in the future. Keywords: Regional Development Bank, bank, financial performance, National Authority for Financial Sector (OJK).